Vegetation structure and species composition of agarwood (Aquilaria spp.) habitats in natural and planted forests in Buru Island, Indonesia - NINGSIE INDAHSUARY UAR; LINA KARLINASARI; ISKANDAR Z. SIREGAR; SETYO PERTIWI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Uar NI, Karlinasari L, Siregar IZ, Pertiwi S. 2025. Vegetation structure and species composition of agarwood (Aquilaria spp.) habitats in natural and planted forests in Buru Island, Indonesia. Biodiversitas 26: 3927-3939. Aquilaria is a genus of agarwood-producing trees that grow almost throughout Indonesia. Buru Island is one of the areas with the presence of Aquilaria spp. species. Currently, information related to the structure and composition of tree species in the habitats of agarwood plants is still limited. This study aimed to describe the structure and composition of tree species in the natural habitat and cultivated area of agarwood plants in three locations in Buru Island, namely Airbuaya, Fena Leisela, and Batabual Sub-districts. Vegetation analysis was carried out by field surveys using a combination of line transect and square plot methods to document plant species and number of individuals at seedling, sapling, pole and tree levels. The results showed that the stand structure of vegetation community at the research location formed an inverted "J" curve. The species composition in the three locations for natural and cultivated habitats were composed by agarwood-producing plants and non-agarwood plants. The Diversity Index in the natural habitat was moderate to high, with a value of 1.08-3.35, while in the cultivated areas had a high Diversity Index, with a value of 2.08-3.57. Both natural and cultivated habitats had an even distribution of species. The species richness index at both natural and cultivated habitats was moderate to high, with a value of 3.60-7.54. The results of the study indicate that both natural forests and cultivated forests in Buru Island have high potential to support the growth of agarwood-producing trees, as evidenced by healthy stand structures and moderate to high diversity and species richness indices. Therefore, sustainable management strategies are necessary, including the conservation of natural forests, the development of agroforestry-based cultivation models, and the optimization of natural regeneration processes.